Editorial Board and Guidelines for the Authors - SOSIOHUMANIKA, Editor Journal (SOSIOHUMANIKA, 2016)
SOSIOHUMANIKA will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment, and analysis on the key issues surrounding the humanities and social sciences education and its various aspects. Analysis will be practical and rigorous in nature.Bandung, Indonesia: November 30, 2016.Prof. Dr. H.R. Asep KadarohmanEditor-in-Chief of the SOSIOHUMANIKA Journal; and Vice Rector UPI for Academic and Students Affairs.Â